On the relationship between rhythm-based temporal expectations and endogenous spatial attention in simple reaction-time tasks - Charras, Pom; Chica, Ana B.; Capizzi, Mariagrazia (Frontiers in Cognition, 2023)
Recent evidence suggests that the temporal expectations afforded by a regular rhythmic structure operate independently from endogenous spatial attention in simple reaction-time tasks. The most common manipulation followed in previous studies consisted of presenting a target stimulus either “in-time” or “out-of-time” (earlier or later) with a preceding rhythm. However, contrary to the proposal of entrainment models predicting a behavioral advantage for in-time compared to both early and late targets, responses were still faster for late targets, according to the so-called “foreperiod effect”. This finding makes it difficult to fully disentangle the impact of rhythm and the benefits afforded by the passage of time on the relationship between rhythm-based temporal and endogenous spatial attention. To shed more light on this issue, we combined a spatial orienting task with a rhythmic manipulation, in which two placeholders flanking the fixation cross flickered at either a regular or irregular pace. Spatial orienting to the target location was deployed by symbolic color cues that were displayed independently of the rhythm (independent cues) or were integrated with the temporal rhythmic cues (integrated cues). Crucially, for both independent and integrated cues, and for regular and irregular rhythms, the interval between the rhythm and the target (i.e., the foreperiod) was kept fixed in Experiments 1-3 to control for the foreperiod effect, while the effect of foreperiod was explored in Experiment 4. Results showed a more beneficial effect of rhythms with independent cues as compared to integrated cues. Additionally, the benefit of rhythms was slightly but significantly larger at valid, compared to invalid, spatial locations, regardless of the foreperiod. Our results extend previous studies by showing that interactive effects of rhythms and endogenous spatial attention may emerge in low-demanding detection tasks.